Bioprospecting Plant Growth-Promoting Rhizobacteria That Mitigate Drought Stress in Grasses - Jochum, Michael D.; McWilliams, Kelsey L.; Borrego, Eli J.; Kolomiets, Mike V.; Niu, Genhua; Pierson, Elizabeth A.; Jo, Young-Ki (Frontiers in Microbiology, 2019)
This study reports the application of a novel bioprospecting procedure designed to screen plant growth-promoting rhizobacteria (PGPR) capable of rapidly colonizing the rhizosphere and mitigating drought stress in multiple hosts. Two PGPR strains were isolated by this bioprospecting screening assay and identified as Bacillus sp. (12D6) and Enterobacter sp. (16i). When inoculated into the rhizospheres of wheat (Triticum aestivum) and maize (Zea mays) seedlings, these PGPR resulted in delays in the onset of plant drought symptoms. The plant phenotype responding to drought stress was associated with alterations in root system architecture. In wheat, both PGPR isolates significantly increased root branching, and Bacillus sp. (12D6), in particular, increased root length, when compared to the control. In maize, both PGPR isolates significantly increased root length, root surface area and number of tips when compared to the control. Enterobacter sp. (16i) exhibited greater effects in root length, diameter and branching when compared to Bacillus sp. (12D6) or the control. In vitro phytohormone profiling of PGPR pellets and filtrates using LC/MS demonstrated that both PGPR strains produced and excreted indole-3-acetic acid (IAA) and salicylic acid (SA) when compared to other phytohormones. The positive effects of PGPR inoculation occurred concurrently with the onset of water deficit, demonstrating the potential of the PGPR identified from this bioprospecting pipeline for use in crop production systems under drought stress.